Modelling of statically loaded single pile taking into account nonlinearity of foundation soil - F. S. Shkoliar; D. V. Rogozinnikova (Vestnik MGSU)
Introduction. Modelling of pile foundations in modern software packages (PC) is often carried out in a linear formulation of the problem and with the use of coefficients that overestimate the results of pile foundations by several times. This approach leads to significant overconsumption of materials and overestimation of the estimated cost of the object under construction. In modern realities, designers are faced with the problem of modelling the design situation, which is closest to the real operation of the pile in the ground, and since the foundation soil is a heterogeneous medium, the calculation must be carried out non–linearly, which is quite time-consuming in software packages. A numerical comparison of full-scale tests of a single pile under static load and calculation in a software package, taking into account the nonlinearity of the foundation soils, is carried out.Materials and methods. The calculations are carried out in the finite element software package LIRA-CAD by modelling the design scheme with volumetric finite elements. The change in the settlement of piles in different soils under step load is analyzed.Results. Numerical experiment of change in the settlement of a single pile using a volumetric finite element model with a given physical nonlinearity of the soil was performed. The obtained results of the numerical experiment are compared with the results of the full-scale experiment.Conclusions. The results of the study show a large discrepancy between the settlements of piles according to field tests and the results of calculations according to SP 24.13330.2021. With the help of modern software packages, it is possible to carry out more accurate calculations. However, the introduction of correction coefficients can bring the calculated situation according to regulatory documents closer to more real conditions of deformation of the foundation soils in the process of preliminary selection.